An affinity-modulated T cell engager targeting Claudin 18.2 shows potent anti-tumor activity with limited cytokine release - D Gareth Rees; Yun He; Scott A Hammond; Mark Cobbold; Nicolas Giraldo; Saso Cemerski; Marina Natoli; Yiping Rong; Jonathan Fitzgerald; Kathy Mulgrew; Simon J Dovedi; Miguel Gaspar; et al. (Journal for ImmunoTherapy of Cancer)
Background AZD5863 is a bispecific T cell engager (TCE) with high affinity to CLDN18.2 and low affinity to cluster of differentiation 3 (CD3), designed to decrease its peripheral cytokine release potential, improve the therapeutic index, and maintain potent anti-tumor activity.Methods AZD5863 was evaluated using CLDN18.2-expressing human cell lines alone or in co-cultures with human or cynomolgus monkey peripheral blood mononuclear cells to determine affinities, specificity, potency, and bystander killing activity. In vivo, AZD5863-mediated tumor growth inhibition and pharmacodynamics were evaluated in humanized mice or human CD3 transgenic mice implanted with CLDN18.2-expressing cancer cell lines.Results AZD5863 was shown to bind specifically to human and cynomolgus monkey CLDN18.2 and to CD3, with CLDN18.2 binding also conserved against the murine protein. AZD5863 mediated T cell-dependent anti-tumor activity against CLDN18.2-expressing lines, with potency significantly correlating with CLDN18.2 receptor density. Cytokine secretion induced by AZD5863, in vitro and in vivo, was lower compared with a CLDN18.2 TCE with higher affinity for CD3. AZD5863 mediated T cell-dependent bystander killing of CLDN18.2-negative cells in the presence of CLDN18.2-expressing cells, in a mechanism partly dependent on interferon gamma (IFNγ), tumor necrosis factor alpha (TNFα), and Fas ligand. In vivo, AZD5863 treatment resulted in potent tumor control in pancreatic, gastric, and esophageal models and enhanced engraftment of immune populations in a humanized model.Conclusions AZD5863 mediates potent anti-tumor activity in vitro and in vivo, while inducing limited levels of cytokines. This work improves our understanding of the mechanism of action of affinity balanced TCEs and informs the design of a phase 1 trial testing AZD5863 in gastric, pancreatic, and esophageal adenocarcinoma (NCT06005493).